Expand (5a - 3b)^3
Pls answer my question and win more points . Good luck
Answers
Answered by
1
Answer:
HeyThere ‼
As we know ,
( x – y )³ = x³ – 3x²y + 3xy² – y³
OROR
( x – y )³ = ( x – y ) ( x² + y² – 2xy )
Now , ( 5a – 3b )³
= (5a)³ – 3(5a)²(3b) + 3(5a)(3b)² – (3b)³
= 125a³ – 225a²b + 135ab² – 27b²
OROR
( 5a – 3b )³
= ( 5a – 3b ) [ (5a)² + ( 3b)² – 2( 5a )( 3b ) ]
= ( 5a – 3b ) ( 25a² + 9b² – 30ab )
Similar questions
Math,
2 months ago
Computer Science,
2 months ago
Math,
2 months ago
Math,
4 months ago
Math,
4 months ago
India Languages,
9 months ago
Computer Science,
9 months ago